2020
DOI: 10.1089/acm.2019.0325
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Standardized Extract of Centella asiatica on Postlaser Resurfacing Wound Healing on the Face: A Split-Face, Double-Blind, Randomized, Placebo-Controlled Trial

Abstract: Background: Centella asiatica, a medicinal plant, has been used traditionally to promote wound healing. Its efficacy on promoting postlaser resurfacing wound healing is lacking.Methods: Thirty individuals with facial acne scars underwent a treatment with 2940 nm Er:YAG laser. Half side of the face was randomized to receive 0.05% w/w ECa 233 gel, a standardized extract of C. asiatica, and the other half a placebo gel. The gels were applied four times daily for 7 days then twice daily for 3 months. Erythema, mel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 23 publications
(26 reference statements)
1
14
0
3
Order By: Relevance
“…All experimental animals showed good tolerability to the test substances after oral and intravenous administration. The results implied that the test substances, especially Centell-S, are safe in animals, a finding that is in line with our previous reports in standardised extract of C. asiatica 14 , 15 , 19 , 23 . After intravenous administration of Centell-S, the plasma concentrations of madecassoside and asiaticoside were slightly lower than after pure compound administration.…”
Section: Discussionsupporting
confidence: 91%
“…All experimental animals showed good tolerability to the test substances after oral and intravenous administration. The results implied that the test substances, especially Centell-S, are safe in animals, a finding that is in line with our previous reports in standardised extract of C. asiatica 14 , 15 , 19 , 23 . After intravenous administration of Centell-S, the plasma concentrations of madecassoside and asiaticoside were slightly lower than after pure compound administration.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast to the abundant in vivo evidence of the wound-healing effect of C. asiatica , clinical studies are sparse. Yet, one clinical trial showed a significant improvement in post-laser-resurfacing wound healing in patients with bilateral atrophic facial acne scars treated with ECa 233 gel for three months compared to the patients in the control group [ 50 ].…”
Section: Pharmacological Effects Of Centella Asiatica On Skin Diseasesmentioning
confidence: 99%
“…Four studies [ 59 , 60 , 61 , 62 ] on C. asiatica were included in the systematic review ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%